Abundance trends and ecology of planktonic ciliates of the south-western Atlantic (35-63°S): A comparison between neritic and oceanic environments - Santoferrara, L. (2009)
Ciliates from sub-surface waters of the Argentine shelf and the Drake Passage under austral summer and autumn conditions were examined and compared for the first time. In both environments, the taxonomic structure of ciliates was related to temperature and salinity, and aloricate oligotrichs dominated in density (80%) over loricate oligotrichs, litostomatids and prostomatids, while the microplanktonic fraction prevailed in terms of biomass (90%) over the nanociliates. Myrionecta rubra was found all along the Argentine shelf only in autumn, but showed isolated peaks of abundance (103 ind. L -1) during summer. Mean values of density and biomass of total ciliates decreased ca. 2-fold from the shelf-slope to oceanic waters, while potential maximum production of aloricate oligotrichs decreased 9-fold, in relation with the drop in chlorophyll a concentration and the latitudinal decline of temperature, also reflected in maximum growth rates. Fifty percent of total ciliate abundance was represented by local increases (maximum: 20 000 ind. L-1 and 25 μg C L-1), which were spatially superimposed with ranges of seawater temperature and chlorophyll a concentrations of 10-15°C and 0.6-6 μg L-1, respectively, and were found in the nearby of fronts located on the shelf and the slope.